Serum Tumor Marker Dynamics as Predictive Biomarkers in NSCLC Chemo-Immunotherapy and Mono-Immunotherapy Maintenance: A Registry-Based Descriptive Study - Lang D (Dove Medical Press, 2020)
David Lang,1,2 Wolfgang Haslinger,2 Kaveh Akbari,2,3 Mario Scala,2,3 Benedikt Hergan,2,3 Christian Asel,2,3 Andreas Horner,1,2 Romana Wass,1,2 Elmar Brehm,1,2 Bernhard Kaiser,1 Bernd Lamprecht1,2 1Johannes Kepler University Hospital, Department of Pulmonology, Linz, Austria; 2Johannes Kepler University, Medical Faculty, Linz, Austria; 3Johannes Kepler University Hospital, Central Radiology Institute, Linz, AustriaCorrespondence: David LangKepler University Hospital, Department of Pulmonology, MedCampus III, Krankenhausstraße 9, Linz 4020, AustriaTel +43 5 7680 83 73797Email david.lang@kepleruniklinikum.atObjective: To evaluate serum tumor markers (STM) as predictive biomarkers in advanced non-small cell lung cancer (NSCLC) treated with chemo-immunotherapy.Methods: Patients having received platinum-based chemo-(CHT) and PD-1/PD-L1-directed immune checkpoint inhibitor (ICI) combination therapy were retrospectively followed. Carcinoembryonic antigen (CEA), carbohydrate antigen 19– 9 (CA19-9), cytokeratin-19 fragments (CYFRA 21– 1) and neuron specific enolase (NSE) were routinely measured at NSCLC diagnosis. The marker with the highest relative elevation was defined “leading STM”, its change was assessed between CHT-ICI as well as mono-ICI maintenance initiation and the respective subsequent restaging. Corresponding computed tomography evaluations were analyzed using response evaluation criteria in solid tumors (RECIST). For CHT-ICI combination and subsequent mono-ICI-maintenance therapy, leading STM and RECIST response were evaluated regarding progression-free (PFS) and overall survival (OS) in Kaplan–Meier analyses.Results: Among 80 CHT-ICI patients (41% women, mean age 63 years), median PFS was 5 months (M;4,9), median OS was 15M (10,/). PFS was significantly (p=0.042) longer, when the leading STM had decreased at first restaging under CHT-ICI combination therapy (9M (5,12; n=41) vs 5M (3,6; n=16)). In the 54 (67.5%) patients who received subsequent mono-ICI maintenance therapy, STM decrease was similarly associated with significantly (p< 0.001) longer PFS (16M (7,/; n=16) vs 3.5M (2,6; n=22)). Patients with radiologically stable or progressive disease and concomitant leading STM decrease had similar PFS in the CHT-ICI combination phase (4M (3,7; n=16) vs 4.5M (2,6; n=14)), but longer PFS in the mono-ICI maintenance setting (13M (7,16; n=10) vs 3M (2,4; n=17)). Median OS was not reached in most subgroups.Conclusion: Leading STM dynamics provide predictive biomarker information additional to radiological response evaluation patients receiving CHT-ICI combination therapy, especially in the mono-ICI maintenance setting.Keywords: carcinoembryonic antigen, platinum doublet chemotherapy, pembrolizumab, CYFRA 21-1, RECIST, nivolumab